Asymmetric warfare in South Asia the causes and consequences of the Kargil Conflict - Lavoy, Peter R. (Peter René), 1961- (Cambridge University Press, 2009)
A unique account of military conflict under the shadow of nuclear escalation, with access to the soldiers and politicians involved.